2022
DOI: 10.1039/d2dt03006c
|View full text |Cite
|
Sign up to set email alerts
|

An unusual zig-zag 2D copper(i) coordination polymer as an outstanding catalyst for azide–alkyne “click” chemistry at room temperature

Abstract: A straightforward method for the synthesis of a two-dimensional (2D) new copper(I) coordination polymer, namely Cu(bzpdc), containing the ligand benzophenone 4,4’-dicarboxylate, and its effective use as catalyst for the azide-alkyne...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Recently, Bilgic et al. performed CuAAC reaction using catalyst Cu(bzpdc) (Table S2, Entry 11) at rt and found a conversion of 98 % with TON 20 and TOF 10 h −1 [17] . Mansano Willig et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Bilgic et al. performed CuAAC reaction using catalyst Cu(bzpdc) (Table S2, Entry 11) at rt and found a conversion of 98 % with TON 20 and TOF 10 h −1 [17] . Mansano Willig et al.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Bilgic et al performed CuAAC reaction using catalyst Cu(bzpdc) (Table S2, Entry 11) at rt and found a conversion of 98 % with TON 20 and TOF 10 h À 1 . [17] Mansano Willig et al reported that only 1 mol % of Cu(INA) 2 (H 2 O) 4 (Table S2, Entry 12) can produce 1-benzyl-4-phenyl-1H-1,2,3-triazole, a, (with 93 % conversion with turnover number (TON) of 100 and turnover frequency (TOF) 500 h À 1 ) within 12 min at 80 °C in solvent-free reaction medium, whereas Cu(INA) 2 -MOF (Table S2, Entry 13) can produce a (with 95 % conversion with TON of 100 and TOF of 1493 h À 1 ) within 4 min under the same reaction condition. [18] The catalytic activity of these catalysts were also studied at rt, solvent-free reaction conditions.…”
Section: One-pot Cuaac Reactionmentioning
confidence: 99%
“…much shorter reaction time, higher TOF value, using water as a sole medium, and ambient reaction condition (Table S3, Supporting Information). For example, COF-based JNM-3-ABC, [24] Cu-TAPB-TFP [47] and Cu@T-D COF, [48] graphdiyne-supported Cu 2 O NCs/GDY, [19] 2Ndoped porous carbon-supported Cu 1 /NC-800, [21] copper(I) coordination polymer [Cu(bzpdc)], [63] and amine-functionalized Cu 30 (MBA) 16 /TiO 2 -NH 2 [64] can also catalyze the above reaction with high conversion, but the reactions need to be carried out in toxic acetonitrile and a longer reaction time or at an elevated temperature.…”
Section: Heterogeneous Catalysis Of Cu(i)-bpy-cof In Azide-alkyne Cyc...mentioning
confidence: 99%
“…They can expand infinitely in one or more dimensions, as 1D chains or 2D and 3D networks. [2][3][4][5] The area of 1D-coordination polymers is one of interest for potential applications in magnetism, 6,7 electrochemistry, 8,9 catalysis, 11 and optoelectronics. 12 The majority of 1D CPs are heteroleptic, with homoleptic systems generally producing 2D or 3D systems.…”
Section: Introductionmentioning
confidence: 99%
“…Minor changes in reaction conditions, ligand design, and the conformational flexibility of the final arrangement of donor atoms of polytopic ligands can lead to significant differences to supramolecular architecture, making it challenging to deliver predictable outcomes. 11 Investigating the consistency of coordination trends of new ligands, provides a frame of reference for their use in larger supramolecular assemblies.…”
Section: Introductionmentioning
confidence: 99%